Nas linhas da literatura: um estudo sobre as representações da escravidão no romance O mulato, de Aluísio Azevedo - Diniz, Leudjane Michelle Viegas (2008)
Throughout this paper, departing from the relation between history and literature, I discuss the representations of slavery present in the novel O mulato, by Aluísio Azevedo. I analyze how slavery and the subjects linked to it are represented in a moment when the intellectuals, thinking of new bases for the nation, inquired the society in which they lived, articulating in a complex way the positivist discussion, which legitimated their discourses in a pattern that could no make it impossible the development of a project of nation, considering the miscegenation of the population. For this study, I dialog with different documentations: newspapers, memory books, letters and mainly the very work O mulato. I evidence different editions of the text, especially the first one, which presents fundamental elements for the understanding of the book repercussion, particularly the critic to slavery in that edition, which assumes different proportions in the subsequent editions.